Luke Nottage & Makoto Ibusuki (eds), Comparing Online Legal Education: Past, Present and Future (Intersentia, 2023) - LEOW, Chin Seng Bryan (Institutional Knowledge at Singapore Management University, 2024)
This is a review of the book Comparing Online Legal Education: Past, Present and Future (Luke Nottage & Makoto Ibusuki, eds) (Intersentia, 2023)